Alcohol and healthy ageing: a challenge for alcohol policy. (July 2017) - Nicholson, D.; McCormack, F.; Seaman, P.; Bell, K.; Duffy, T.; Gilhooly, M.
Abstract: Objectives: This paper presents findings of a qualitative study of older people's use of alcohol during retirement and identifies ways that an improved understanding of older people's drinking can inform policy approaches to alcohol and active and healthy ageing. Study design: Qualitative semi-structured interviews conducted with a self-selecting sample of retired people. Methods: Participants were recruited from three geographical locations in the West of Scotland. A quota sampling design was used to ensure a broad spread of participants in terms of socio-economic position, age and gender. In total 40 participants were interviewed and the data analysed thematically using Braun and Clarke's (2006) approach. Results: Amongst those who used alcohol, it was most often framed in terms of pleasure, relaxation, socialising and as a way to mark the passage of time. Alcohol was often associated with social occasions and interactions both in private and in public spaces. There were also many examples of the use of imposed routines to limit alcohol use and of a decreasing volume of alcohol being consumed as participants aged. This suggests that older people are often active in constructing what they regard as 'healthier' routines around alcohol use. However, processes and circumstances associated with ageing can lead to risk of social isolation and/or increased alcohol consumption. Such processes include retirement from paid work and other 'biographical disruptions' such as caring for a partner, bereavement and/or loss of social networks. Conclusions: These findings highlight processes that can result in changes in drinking habits and routines. Whilst these processes can be associated with a reduction or cessation of alcohol use as people age, they can also be associated with increased risk of harmful alcohol consumption. Fractured or disrupted routines, particularly those associated with bereavement or the burden of caring responsibilities, through increasing the risk of loneliness and isolation, can construct increased risk of harmful alcohol consumption. These findings reframe the pathway of risk between ageing and alcohol-related harm by highlighting the vulnerability to harmful drinking practices brought by fracture or sudden change of routine. The findings point to a role for public health in supporting the reconstruction of routines that provide structure and meaning and can be used to actively manage the benefits and harms associated with drinking. Highlights: The study suggests older people are often active in constructing what they view as 'healthier' routines around alcohol use. The disruption to patterned routines associated with major life events can prompt changes in alcohol drinking habits. The results reframe the pathway of risk between ageing and alcohol-related harm by stressing the role of change of routine. The study suggests a role for public health in aiding reconstruction of routines to manage the harms associated with drinking.